Early riser - Fforde, Jasper (Viking, 2018)
"Imagine a world where all humans must hibernate through a brutally cold winter, their bodies dangerously close to death as they enter an ultra-low metabolic state of utterly dreamless sleep. All humans, that is, apart from the Winter Consuls, a group of officers who diligently watch over the vulnerable sleeping citizens. Charlie Worthing is a novice, chosen by a highflying hero Winter Consul to accompany him to the Douzey, a remote sector in the middle of Wales, to investigate a dream which is somehow spreading amongst those in the hibernational state, causing paranoia, hallucination and a psychotic episode that can end in murder. Worthing has been trained to deal with Tricksy Nightwalkers whose consciousness has been eroded by hibernation, leaving only one or two skills and an incredible hunger; he's been trained to stay alive through the bleakest and loneliest of winters - but he is in no way prepared for what awaits him in Sector Twelve. There are no heroes in Winter, Worthing has been told. And he's about to find out why."--Publisher's description.